Hotel Strategy in Facing the Covid-19 Pandemic (The Westin Resort Nusa Dua Experience) - Ni Putu Lianda Ayu Puspita; I Putu Astawa; I Gede Mudana (International Journal of Glocal Tourism, 2021)
Purpose: This research is conducted with the aim of examining the management strategy of a hotel in a Covid-19 pandemic situation. Research methods: The research method used is descriptive qualitative with virtual interview techniques and literature study. Findings: The strategy adopted by the hotel, in this case The Westin Resort Nusa Dua is a generic strategy and a corporate functions strategy. Implication: The strategy is expected to become a reference for other hotels during the Covid-19 pandemic so that the hotels can still operate even in abnormal conditions.